From Cell Death to Regeneration: Rebuilding After Injury - Guerin, Dylan J.; Kha, Cindy X.; Tseng, Kelly Ai-Sun (Frontiers in Cell and Developmental Biology, 2021)
The ability to regrow lost or damaged tissues is widespread, but highly variable among animals. Understanding this variation remains a challenge in regeneration biology. Numerous studies from Hydra to mouse have shown that apoptosis acts as a potent and necessary mechanism in regeneration. Much is known about the involvement of apoptosis during normal development in regulating the number and type of cells in the body. In the context of regeneration, apoptosis also regulates cell number and proliferation in tissue remodeling. Apoptosis acts both early in the process to stimulate regeneration and later to regulate regenerative patterning. Multiple studies indicate that apoptosis acts as a signal to stimulate proliferation within the regenerative tissues, producing the cells needed for full regeneration. The conservation of apoptosis as a regenerative mechanism demonstrated across species highlights its importance and motivates the continued investigation of this important facet of programmed cell death. This review summarizes what is known about the roles of apoptosis during regeneration, and compares regenerative apoptosis with the mechanisms and function of apoptosis in development. Defining the complexity of regenerative apoptosis will contribute to new knowledge and perspectives for understanding mechanisms of apoptosis induction and regulation.